A microheater on polyimide substrate for hand-held realtime microfluidic polymerase chain reaction amplification - Dae-Sik Lee; Ok Ran Choi; Yujin Seo (Micro and Nano Systems Letters, 2019)
Abstract The development of a DNA microfluidic device with a high speed, low power, and low reagent volume is very critical for real-time genotyping and diagnosis in point-of-care applications. This paper reports a polymer-based thermal cycler for a handheld and battery-powered polymerase chain reaction (PCR) system using a polyimide (PI) film-based micro-fabricated heater module and polymer film microfluidic chambers of 10 μL, with a handheld and low power consumption, compared to state of the art. It took 21 min for 40 thermal cycling for DNA amplification and a maximum power consumption of 0.6 W. The microheater on PI film substrate fabricated and real-time quantification of deoxyribonucleic acid (DNA) using the heater in hand-held sizes experimentally shown here. The device would be applicable for on-site molecular diagnostics.